The effects of dexamphetamine on the resting-state electroencephalogram and functional connectivity - Albrecht, Matthew; Roberts, G.; Price, G.; Lee, J.; Iyyalol, R.; Martin-Iverson, M. (2015)
© 2015 Wiley Periodicals, Inc. The catecholamines-dopamine and noradrenaline-play important roles in directing and guiding behavior. Disorders of these systems, particularly within the dopamine system, are associated with several severe and chronically disabling psychiatric and neurological disorders. We used the recently published group independent components analysis (ICA) procedure outlined by Chen et al. (2013) to present the first pharmaco-EEG ICA analysis of the resting-state EEG in healthy participants administered 0.45 mg/kg dexamphetamine. Twenty-eight healthy participants between 18 and 41 were recruited. Bayesian nested-domain models that explicitly account for spatial and functional relationships were used to contrast placebo and dexamphetamine on component spectral power and several connectivity metrics. Dexamphetamine led to reductions across delta, theta, and alpha spectral power bands that were predominantly localized to Frontal and Central regions. Beta 1 and beta 2 power were reduced by dexamphetamine at Frontal ICs, while beta 2 and gamma power was enhanced by dexamphetamine in posterior regions, including the parietal, occipital-temporal, and occipital regions. Power-power coupling under dexamphetamine was similar for both states, resembling the eyes open condition under placebo. However, orthogonalized measures of power coupling and phase coupling did not show the same effect of dexamphetamine as power-power coupling. We discuss the alterations of low- and high-frequency EEG power in response to dexamphetamine within the context of disorders of dopamine regulation, in particular schizophrenia, as well as in the context of a recently hypothesized association between low-frequency power and aspects of anhedonia.